Bisnis Dan Hak Asasi Manusia Di Indonesia: Membangun Konteks Dengan Lensa Pencegahan Kekejaman Massal - Citrawan, Harison (UI Scholars Hub, 2020)
Some efforts to contextualize the United Nations Guiding Principles on Business and Human Rights in Indonesia have been dominated by normative compliance review on the existing national regulations to the norms enshrined under the Principles. This article shall be divided into three parts, commencing from a brief socio-historical description on the landscape of law and development in Indonesia; along with how law and human rights adapted towards the relation between state and corporation since the colonial era. The analysis shall proceed to the types of human rights violation as a result of corporations activities, specifically in natural resource extraction sector. Lastly, an analysis shall be directed to the potential application of mass atrocity lens as a part of integrative efforts on the business and human rights principle into Indonesias context.